Ruins as an affordance - V. V. Zolotukhin (Шаги, 2022)
A review of:Murray, S. (2020). Performing ruins. Palgrave Macmillan. 316Corrieri, A. (2016). In place of a show: What happens inside theatres when nothing is happening. Bloomsbury Methuen Drama. 198